Larangan Penggunaan Klausul Baku Tertentu dalam Perjanjian antara Konsumen dan Pelaku Usaha - Ahmadi Miru (Jurnal Hukum IUS QUIA IUSTUM, 2001)
The Consumer Protection Act (UUPK), that initially became the hope for consumers and frightened business actors (producers) due to its threat ofsanctions, after two years having been declared to bein effect, did not show any significant indication that the Act alreadyprovided protections to consumers. Despite the fact that the ineffectiveness ofacts Is generally due to three factors, namely, implementing agents ofthe act (structure), the substance ofthe act (substance), and society subject to the act(culture), tha merely questioning ofthe substance ofthis act, especially Article 18Paragraph (1) that prohibits theattachment ofthestandard clauses, was because the article contains many defect making the actcould not ordifficult to be obeyed, unless perfection is made to it.Therefore, to be effective, perfection should bemade to Article 18 Paragraph (1) ofthe UUPK as well as orther articles containing defects. Similarly, prohibition ofattachment shouldnotbe applied merely onthestandardclausesbutalsothenon-standard clauses that infict any loss upon consumers as regulated by Article 18 Paragraph (1) ofUUPK.Beside theperfection oftheact (UUPK) in order that consumers should notbesuffered losses causedbyproducers, what should be performed would be consumer's educa tion, theunity ofconsumers, andthe implementation ofa good faith.